Technology-assisted rehabilitation following total knee or hip replacement for people with osteoarthritis: a systematic review and meta-analysis - Wang, Xia; Hunter, David J.; Vesentini, Giovana; Pozzobon, Daniel; Ferreira, Manuela L. (Bmc, 2019)
Background: To evaluate the effectiveness and safety of technology-assisted rehabilitation following total hip/knee replacement (THR/TKR). Methods: Six electronic databases were searched without language or time restrictions for relevant studies: MEDLINE, EMBASE, Cochrane Library, CINAHL, SPORTDiscus, Physiotherapy Evidence Database (PEDro); from inception to November 7th, 2018. Two reviewers independently applied inclusion criteria to select eligible randomised controlled trials (RCTs) that investigated the effectiveness of technology-based interventions, compared with usual care or no intervention for people undergoing THR/TKR. Two reviewers independently extracted trial details (e.g. patients' profile, intervention, outcomes, attrition and adverse events). Study methodological quality was assessed using the PEDro scale. Quality of evidence was critically appraised using the Grading of Recommendations, Assessment, Development and Evaluation approach. Results: We identified 21 eligible studies assessing telerehabilitation, game- or web-based therapy. There were 17 studies (N = 2188) in post- TKR rehabilitation and 4 studies (N = 783) in post- THR rehabilitation. Compared to usual care, technology-based intervention was more effective in reducing pain (mean difference (MD): - 0.25; 95% confidence interval (CI): - 0.48, - 0.02; moderate evidence) and improving function measured with the timed up-and-go test (MD: -7.03; 95% CI: - 11.18, - 2.88) in people undergoing TKR. No between-group differences were observed in rates of hospital readmissions or treatment-related adverse events (AEs) in those studies. Conclusion: There is moderate-quality of evidence showed technology-assisted rehabilitation, in particular, telerehabilitation, results in a statistically significant improvement in pain; and low-quality of evidence for the improvement in functional mobility in people undergoing TKR. The effects were however too small to be clinically significant. For THR, there is very limited low-quality evidence shows no significant effects.
Keywords: Joint arthroplasty; Healthcare delivery; Telerehabilitation; Digital health; Virtual reality